DOI: 10.3990/1.9789036546867
|View full text |Cite
|
Sign up to set email alerts
|

Improving the modelling of response variation in international large-scale assessments

Abstract: Evolving from early ILSAs such as the First International Mathematics and Science Study (FIMSS; Husén, 1967), TIMSS has the longest tradition and is IEA's most wellknown ILSA, with 49 participating countries in recent cycles (Mullis, Martin, Foy, & Hooper, 2016). Every four years it assesses students in Grade 4 and 8 on their math and science skills. TIMSS is often said to be "curriculum-based", because it uses a curriculum model consisting of the intended, implemented and attained curriculum. These three aspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…The second and third research question were addressed by including gender or reading demand (only for mathematics) to the model. The categorisation of Punter, Meelissen, and Glas (2018) of the TIMSS 2015 mathematic items was used to classify the mathematics items in a low, medium or high level of reading demand.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The second and third research question were addressed by including gender or reading demand (only for mathematics) to the model. The categorisation of Punter, Meelissen, and Glas (2018) of the TIMSS 2015 mathematic items was used to classify the mathematics items in a low, medium or high level of reading demand.…”
Section: Discussionmentioning
confidence: 99%
“…The study also examined the occurrence of a mode effect between mathematics items with a high, medium or low reading demand (Mullis et al, 2013;Punter et al, 2018). The literature review suggested that the complexity and length of reading texts on a computer or tablet screen were two of the main disadvantages of CBT and could be related to the lower performance of students on CBTs compared to PBTs (Choi & Tinkler, 2002;Kingston, 2009;Ling, 2016;Mangen et al, 2013;Nardi & Ranieri, 2018).…”
Section: British Journal Of Educational Technology Vol 51 No 6 2020mentioning
confidence: 99%
See 1 more Smart Citation